From Nongkrong to Transaction: the Role of Nongkrong Culture In Shaping Generation Z’s Purchasing Behavior In Coffee Shops - Dominikus Aditya Putra Pradana; Yosephine Dwi Hayu Agustini, Maria (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to explore the definition of the nongkrong culture and the key elements that shape it, as well as to analyze its role in influencing Generation Z’s purchasing behavior in coffee shops. A qualitative approach using the literature review method was employed to examine the depth and breadth of the topics studied—namely, nongkrong culture and purchasing behavior. Scientific literature was sourced from national and international journals. Through an article selection process, 27 articles were identified and used as research sources. This study identifies the definition of nongkrong culture as the habit of young people gathering in coffee shops to socialize, fulfill lifestyle needs, express themselves, follow social media trends, and unwind. From this definition, it is found that lifestyle, social interaction, and social media constitute the key elements shaping nongkrong culture. Furthermore, nongkrong culture plays both an active and symbolic role in influencing purchasing behavior. This study provides new insights by offering a more comprehensive and academically grounded definition of nongkrong culture, accompanied by a detailed explanation of its key formative elements—all of which collectively enrich the theoretical understanding of youth social behavior and can serve as a solid foundation for more in-depth and systematically structured future research.